Tangible Chess for Dementia Patients – Playing with Conductive 3D Printed Figures on a Touchscreen - Eichhorn, Christian; Plecher, David A.; Golovnya, Oleksandr; Volkert, Dorothee; Hiyama, Atsushi; Klinker, Gudrun (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2021)
In the area of dementia care, Serious Games are seen as an opportunity to boost cognitive capabilities and to stabilize the ability to independently perform Activities of Daily Living (ADLs). We developed a Serious Game based on the popular boardgame chess to target the elderly and dementia patients through incorporating dementia relevant requirements. We analyzed multiple chess variants, which use a smaller board size with less pieces to reduce the game complexity. This results in a new chess version, that helps players to understand the core mechanics of the game and allows them to get into the flow of playing with chess figures. Included are different training scenarios as well as a virtual opponent, that adjusts towards the cognitive skill level of a dementia patient. The game’s visual appearance can be tailored to any person and preference by e.g. adjusting the board color theme to address color blindness or changing between 2D and 3D modes. Another core aspect of our game concept focuses on custom 3D printed chess pieces. They are made from conductive material and have a unique finish with additional accessories to distinguish individual pieces from each other. This results in a natural, tangible playing experience on a touchscreen device, a so-called Tangible User Interface. Besides connecting to the feeling of playing real chess, such an approach has the potential to reduce the fear towards modern devices, a well-known entry barrier for this target group. In a retirement home a small pilot study with dementia patients is performed. Furthermore, by utilizing a user-centered approach, we can identify additional insights into the concept of a supported boardgame with tangible game figures which can overcome fear towards modern technology.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 3D printing; AI; Alzheimer; Chess; Cognitive training; Dementia; HCI; Serious Games; Tangible User Interface; Tangibles